Old Age and Aging: Presence and Absence in the Plays of Brian Friel - Tallone, Giovanna (Hungarian Journal of English and American Studies, 2020)
Old age and aging may not seem an immediate priority in Brian Friel’s drama, yet several plays feature memorable characters of old, elderly, aging, or declining people, whose presence on stage is occasionally revealed through their absence. The growing cultural visibility of older people contrasts with their invisibility as useless members of society: they are physically present, yet invisible. In Friel’s dramaturgy, this arouses reflection on the role of old age absent from the mimetic space and relegated to the diegetic space offstage; absence as a theatrical device marks offstage characters as potential catalysts for action. If in some plays elderly characters remain in the background, in others they become pivotal to dramatic construction, ranging from dominant figures like Columba in The Enemy Within (1962), to tyrannical ones such as Manus in The Gentle Island (1971) and Father in Aristocrats (1979), to social outcasts in The Loves of Cass McGuire (1967) and Dancing at Lughnasa (1990). This essay considers the variety of ways in which Friel introduces or openly deals with the issues of aging and of old age through stagecraft and varied dramatic choices as well as the manipulation of mimetic and diegetic space in terms of presence and absence in particular. (GT)